European Society of Endocrinology Clinical Practice Guidelines for the management of aggressive pituitary tumours and carcinomas. Issue 1 (January 2018) - Raverot, Gerald; Burman, Pia; McCormack, Ann; Heaney, Anthony; Petersenn, Stephan; Popovic, Vera; Trouillas, Jacqueline; Dekkers, Olaf M; ,
Abstract : Background: Pituitary tumours are common and easily treated by surgery or medical treatment in most cases. However, a small subset of pituitary tumours does not respond to standard medical treatment and presents with multiple local recurrences (aggressive pituitary tumours) and in rare occasion with metastases (pituitary carcinoma). The present European Society of Endocrinology (ESE) guideline aims to provide clinical guidance on diagnosis, treatment and follow-up in aggressive pituitary tumours and carcinomas. Methods: We decided upfront, while acknowledging that literature on aggressive pituitary tumours and carcinomas is scarce, to systematically review the literature according to the GRADE (Grading of Recommendations Assessment, Development and Evaluation) system. The review focused primarily on first- and second-line treatment in aggressive pituitary tumours and carcinomas. We included 14 single-arm cohort studies (total number of patients = 116) most on temozolomide treatment ( n = 11 studies, total number of patients = 106). A positive treatment effect was seen in 47% (95% CI: 36–58%) of temozolomide treated. Data from the recently performed ESE survey on aggressive pituitary tumours and carcinomas (165 patients) were also used as backbone for the guideline. Selected recommendation: (i) Patients with aggressive pituitary tumours should be managed by a multidisciplinary expert team. (ii) Histopathological analyses including pituitary hormones and proliferative markers are needed for correct tumour classification. (iii) Temozolomide monotherapy is the first-line chemotherapy for aggressive pituitary tumours and pituitary carcinomas after failure of standard therapies; treatment evaluation after 3 cycles allows identification of responder and non-responder patients. (iv) In patients responding to first-line temozolomide, we suggest continuing treatment for at least 6 months in total. Furthermore, the guideline offers recommendations for patients who recurred after temozolomide treatment, for those who did not respond to temozolomide and for patients with systemic metastasis.